P11: (18)FDG-PET/CT for early prediction of response to first line platinum chemotherapy in advanced thymic epithelial tumors - Palmieri, Giovannella (J Thorac Dis, 2015)
BACKGROUND: To investigate the value of the metabolic tumor response assessed with (18)F-fluorodeoxyglucose positron emission tomography (FDG-PET), compared with clinicobiological markers, to predict the response disease to first line platinum based chemotherapy in advanced thymic epithelial tumors (TETs). METHODS: Twenty patients with diagnosis of TET and stage of disease III and IV sec, Masaoka-Koga, were retrospectively included in this monocentric study. Different pre-treatment clinical, biological and pathological parameters, including histotype sec, WHO 2004 and stage of disease sec, Masaoka-Koga were assessed. Tumor glucose metabolism at baseline and its change after the first line platinum based chemotherapy (from 4 to 6 cycles) were assessed using FDG-PET, moreover the response disease was assessed using total body CT scan for the evaluation of RECIST criteria 1.1. RESULTS: Twelve patients had an objective response to the first line platinum based chemotherapy according RECIST criteria 1.1 and all of them started with a SUV(max) at baseline major than 5, indeed the other eight patients, non-responders to chemotherapy, had a SUV(max) at baseline minor than 5. CONCLUSIONS: It is important to define the chemosensitivity of advanced TETs early. Combining bio-pathological parameters with the metabolism at baseline assessed with FDG-PET can help the physician to early predict the probability of obtaining a disease response to first line platinum based chemotherapy. The SUV(max) cut off of 5 at (18)FDG-PET/CT performed at baseline treatment might be a new parameter for choosing the most powerful first line of chemotherapy. Given these results, further prospective studies are needed to establish a new first line therapy in advanced TETs with a low SUV(max) at baseline, non-responders to conventional chemotherapy.